ZAKAT AND EDUCATION FOR POVERTY ALLEVIATION AND INCOME INEQUALITY REDUCTION: A CASE STUDY OF WEST JAVA, INDONESIA - Qurroh Ayuniyyah; Ataul Huq Pramanik; Norma Md. Saad; Muhammad Irwan Ariffin (STES Islamic Village, 2019)
This study attempts to investigate the role of zakat for poverty alleviation and income inequality reduction based on the educational background of the zakat beneficiaries in three different regions including Bogor, Depok and Sukabumi Indonesia by using CIBEST model, Gini coefficient and Atkinson index. It takes the case study of 1309 households zakat recipients managed by the national zakat board (BAZNAS) in each city and regency under consideration. This study suggests that the existences of zakat distribution programs after one year appear to have better effect in terms of poverty alleviation and income inequality reduction on the household heads who attend formal and informal schools as compared to the household heads who never attain such educational backgrounds.